The Cheeses of Italy: Science and Technology - Gobbetti, Marco (Springer International Publishing, 2018)
This book contains a detailed description of the historical aspects of cheese manufacture, historical information on the most traditional and popular Italian cheese varieties. An overview of cheese production is included, covering the main general aspects. An overall classification of Italian cheeses follows, which categorizes all the cheese varieties that have a tradition and/or an economic importance. Based on a large literature review, the core of the book includes descriptions of cheese- making traits which are unique to Italian cheeses. In particular, the chemical composition of milk, the use whey or milk natural starters, some technology options (e.g., curd cooking), the microbiota composition and metabolism during curd ripening, especially for cheese made from raw milk, and the main relevant biochemical events, which occur during the very long-time ripening, are described. The last part of the book provides a detailed description of the biotechnology for the manufacture of the most traditional and popular Italian cheeses.